FIDIC quick reference guide. - Barr, Brian; Grutters, Leo (ICE Publishing, 2015)
In a perfect world, projects are completed on time and on budget, affording the beneficiaries the advantages of the designed project. As long as contracting is the modus operandi, such a scenario can only occur through efficient and effective use of those contracts. Quality contract administration is of paramount importance. Numerous books have been written on this subject with the aftermath of contractual conflict in mind. Such books dwell on the methods by which disputes can be resolved, with emphasis placed on the legal aspects of contract administration. ' The FIDIC Quick Reference Guide' takes a different approach. Rather than solving a problem after the conflict has occurred, this series of books and associated electronic aids set out how to prevent the problem from occurring in the first place.